PEMETAAN DENGAN QGIS DAN PERHITUNGAN KORELASI FAKTOR YANG MEMPENGARUHI HASIL PRODUKSI PERTANIAN DENGAN PEARSON CORRELATION - Arie Rachmad Syulistyo; Milyun Ni’ma Shoumi (Informasi Interaktif, 2021)
Food affects the nation stability. The Indonesian government strive continually to maintain food security in the form of policies and research in the agricultural sector. In line with the government's vision and mission, this research was conducted to map and study the relationship between soil conditions, irrigation areas, and harvested areas with corn, soybean and rice yields that can be used to support policy making. Based on the experiment results obtained several factors that influence crop yields, namely soil conditions, weather, and area of harvest. Mapping was done using Quantum GIS (QGIS) and correlation calculations performed using pearson correlation. Based on the analysis result of soil types, temperature and soil area affect crop yields with the highest value of 0.99. The correlations analyzed were the correlation between yield and rice temperature and the correlation between rice yield and cultivated area.Keywords: QGis, food security,pearson correlation.